Ala vestibuloplasty improves cardiopulmonary and activity‐related parameters in brachycephalic cats. Issue 4 (7th March 2023) - Gleason, Hadley E.; Phillips, Heidi; Fries, Ryan; Keating, Stephanie; Hamel, Phillip; McCoy, Annette
Abstract: Objective: To evaluate the effects of ala vestibuloplasty on cardiopulmonary and lifestyle‐related parameters in brachycephalic (BC) cats. Study design: Prospective cohort. Animals: Client‐owned BC cats ( n = 19). Methods: Cats were assessed preoperatively by airway computed tomography (CT), endoscopy, contrast echocardiography, cardiac biomarkers, and structured owner questionnaire. Ala vestibuloplasty was performed bilaterally, and blood values, imaging, and owner questionnaire responses were re‐evaluated 8‐20 weeks postoperatively. Results: Cats were presented for predominantly respiratory clinical signs attributable to brachycephaly. Preoperatively, all cats had stenotic nares, prolonged normalized pulmonary transit time (nPTT) (mean 5.43 ± 1.10 s), and a hyperattenuating pulmonary pattern. No complications occurred following surgery. Postoperatively, nPTT (mean 3.89 ± 0.74 s, p < .001) and frequencies of sneezing ( p = .002), snoring ( p = .006), open‐mouth breathing ( p = .0004), and nasal discharge ( p = .019) were decreased. Cats exhibited increased activity ( p = .005), less frequent dyspnea during activity ( p < .001), longer duration of activity before becoming dyspneic ( p = .002), faster recovery from activity ( p < .001), and decreased respiratory noise ( p < .001). Median questionnaire scores improved from preoperative to postoperative ( p < .001). Conclusion: Anatomic, echocardiographic, and CT changes were common in this cohort of clinically affected BC cats. Pulmonary blood flow and respiratory function were improved after surgery. Clinical significance: Stenotic nares are the predominant airway abnormality in BC cats. Ala vestibuloplasty is a safe procedure that improves cardiac and CT abnormalities and respiratory and other clinical signs in BC cats.